2018
DOI: 10.1089/jmf.2017.3941
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis-Stimulating Peptide from Soybean Protects Against High Fat Diet-Induced Apoptosis in Skeletal Muscles

Abstract: Obesity is generally associated with low-grade chronic inflammation that involves the recruitment of macrophages and other inflammation factors to the adipocytes of obese individuals. Tumor necrosis factor-alpha (TNF-α), a cytokine associated with systemic inflammation, is elevated in conditions of obesity. TNF-α is an important factor that plays an important role in skeletal muscle wasting. Apoptosis of myonuclei contributes to the loss of muscle mass and therefore plays an important role in skeletal muscle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Next, we investigated the heterogeneity in gene expression patterns in the skeletal muscle of NAFLD and NASH mice. For 280 DEGs uniquely changed in the skeletal muscle of the NAFLD group of mice (Figure 6A), the GO and KEGG analysis reveal that NF-kB transcription factor activity and apoptotic processes were uniquely upregulated (Figures 6B, D), suggesting inflammatory and apoptotic events that happen in the early stage of liver diseases as reported previously (35); meanwhile, chronic aerobic exercise could ameliorate it (36). Besides this, we found that response to toxic substance, regulation of growth, angiogenesis, axis specification as well as HIF-1 signaling pathway, mineral absorption, PI3K-Akt signaling pathway were enriched in NAFLD uniquely downregulated genes (Figures 6C, E), suggesting that the skeletal muscle may exhibit a disturbance in response to a toxic substance and muscle growth.…”
Section: Analysis Of Unique Gene Programs In Nafld and Nash Micesupporting
confidence: 73%
“…Next, we investigated the heterogeneity in gene expression patterns in the skeletal muscle of NAFLD and NASH mice. For 280 DEGs uniquely changed in the skeletal muscle of the NAFLD group of mice (Figure 6A), the GO and KEGG analysis reveal that NF-kB transcription factor activity and apoptotic processes were uniquely upregulated (Figures 6B, D), suggesting inflammatory and apoptotic events that happen in the early stage of liver diseases as reported previously (35); meanwhile, chronic aerobic exercise could ameliorate it (36). Besides this, we found that response to toxic substance, regulation of growth, angiogenesis, axis specification as well as HIF-1 signaling pathway, mineral absorption, PI3K-Akt signaling pathway were enriched in NAFLD uniquely downregulated genes (Figures 6C, E), suggesting that the skeletal muscle may exhibit a disturbance in response to a toxic substance and muscle growth.…”
Section: Analysis Of Unique Gene Programs In Nafld and Nash Micesupporting
confidence: 73%
“…But the effect of exercise training on NAFLD associated hepatic and cardiac abnormalities are not very clear yet. Interestingly, our recent studies reveal that alcalase derived potato protein hydrolysates (APPH) with lipolysis-stimulating activity and their derivatives were found to possess efficient antiobesity and cyto-protective potentials [1,26,[28][29][30][31]. To investigate the modalities of fatty liver diseases and potential therapeutic interventions various diet based murine models were used in previous studies that elucidated the therapeutic potentials of protein hydrolysates from soy or potato [1,32,33].…”
Section: Agingmentioning
confidence: 99%
“…Novel black soy peptides activated leptin-like signaling and AMP-activated protein kinase in a study for acute effects of black soy peptides on food intake and body weight in rats (78). Recently, Ashokan et al (79) reported a peptide (ValHisValVal) from soybean responsible for stimulating lipolysis in apoptotic skeletal muscles caused by high fat diet. ValHisValVal peptide also regulated TNF-α expression which was elevated due to a high fat diet and suppressed apoptosis-related proteins.…”
Section: Food Peptidesmentioning
confidence: 99%